2012
DOI: 10.3109/13697137.2012.672843
|View full text |Cite
|
Sign up to set email alerts
|

Dydrogesterone does not reverse the cardiovascular benefits of percutaneous estradiol

Abstract: Both HRT groups showed a reduction in their Framingham score. In contrast to data from other HRT investigations on cardiovascular risk, these formulations proved to be safe, even in the first year of use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…The data suggested that continuously applied dydrogesterone in combined-HRT did not diminish the beneficial effects on lipid metabolism induced by estrogens. Similar results were observed in other studies [ 51 59 ]. Overall, when given in combination with estrogen, dydrogesterone does not have a large impact on estrogen effects.…”
Section: Clinical Effects Of Progestogens On Blood Lipids In Hrtsupporting
confidence: 93%
“…The data suggested that continuously applied dydrogesterone in combined-HRT did not diminish the beneficial effects on lipid metabolism induced by estrogens. Similar results were observed in other studies [ 51 59 ]. Overall, when given in combination with estrogen, dydrogesterone does not have a large impact on estrogen effects.…”
Section: Clinical Effects Of Progestogens On Blood Lipids In Hrtsupporting
confidence: 93%
“…One opinion is that progesterone, DG or 17-hydroxyprogesterone caproate are drugs that do not produce some of the adverse effects associated with other progestogens [ 20 ], and DG exerts endothelial anti-inflammatory actions (i.e., via a decrease in expression of leukocyte adhesion molecules) [ 20 ], perhaps linking with modulation of oxidative stress. Clinical studies have also found that DG treatment could improve oxidative stress conditions in combination with E2 [ 21 ]. The DG component offers endometrial protection and cycle control without negating the vasoprotective effects of E2 [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“… 32 In a longitudinal analysis, metabolic parameters (lipid and glucose levels) were similarly improved among women treated for a least 2 years with transdermal estrogen with or without dydrogesterone, indicating no attenuation by dydrogesterone of estrogen-induced beneficial effects. 57 …”
Section: Special Situationsmentioning
confidence: 99%